Transition-metal free highly selective aerobic oxidation of hindered 2-alkylindoles. Issue 34 (26th August 2015) - Shiri, Morteza; Farajpour, Behnaz; Bozorgpour-Savadjani, Zahra; Shintre, Suhas A.; Koorbanally, Neil A.; Kruger, Hendrik G.; Notash, Behrouz
Abstract: A novel and easy access to highly complex 3-oxoindolin-2-ylidene derivatives from the exposure of Ugi-adducts bearing an indolyl moiety in Cs2 CO3 /DMF to air is reported. This is the first example of aerobic oxidation of 2-alkylindoles to 3-oxoindolin-2-ylidenes. Some advantages of this method are the use of air as oxygen source, transition metal-free reagents and simple conditions, a multicomponent and one-pot process and highly regio- and stereoselective manner to trans -3-oxoindolin-2-ylidenes. Graphical abstract: